Pharmaceutical research in paediatric populations and the new EU Paediatric Legislation: an industry perspective - Auby Philippe (BMC, 2008)
Abstract A large proportion of medicines used in children are prescribed off-label, and children have often been denied access to new or innovative medications. Because such situation is unethical, the need to obtain paediatric information for medicines used in children seems nowadays a matter of consensus on a global basis. Based on this, it was clear in EU, like what has happened in the US, that there was a need for a legal obligation for Pharmaceutical Companies to perform studies. This new European Paediatric Regulation that entered into force in 2007 opens a new era of European drug regulatory history and will offer a major opportunity to improve children's health through advancements in research by providing a new framework for evaluating the efficacy and safety of medicines for children. But, paediatric development remains challenging and the hurdles of conducting research in paediatric population are numerous. The article presents the new European Paediatric Regulation, illustrates its rationale through paediatric psychopharmacology, and discusses some of its consequences on paediatric research from an industry perspective. Recommendations for further international collaboration are also suggested to make global paediatric development plans.